PENGELOLAAN FASILITAS TERMINAL SEKAPUR SIRIH OLEH UNIT PELAKSANAAN TEKNIS DAERAH (UPTD) TERMINAL DINAS PERHUBUNGAN DI BAGANSIAPIAPI KABUPATEN ROKAN HILIR TAHUN 2025 - Putra, M. Agus; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
A terminal is a vital facility or infrastructure for managing land transportation in a region, ensuring that land transportation flows in an orderly manner. In accordance with Law No. 22 of 2009 on traffic and road transportation regulations, Rokan Hilir Regency Regulation No. 17 of 2011 sets forth procedures and operational and management standards for terminals. All regulatory frameworks issued by the central and local governments—as part of efforts to manage terminals across all regions, including Rokan Hilir Regency—can be effectively implemented. The objective of this study is to analyze the management of the Sekapur Sirih terminal facility by the Regional Technical Implementation Unit (UPTD) in Bagansiapiapi, Rokan Hilir Regency. This study employs a descriptive qualitative research approach, utilizing interviews, documentation, and observation as data collection methods. The results indicate that the management of the Sekapur Sirih Terminal in Bagansiapiapi, Rokan Hilir Regency, has not been optimized. In terms of terminal planning activities, most aspects have not been implemented effectively. There are several planning aspects, such as the arrangement of passenger and cargo facilities, the display of route and fare schedules, and the scheduling of terminal staff; however, these aspects are also not functioning optimally. In terms of implementation, nearly all related activities are also not functioning well. Out of 9 implementation aspects, only the arrangement of waiting areas and the flow of public vehicles at the terminal is still operational; however, these areas are not utilized in accordance with standard regulations. Regarding supervision, generally, all supervision aspects stipulated in the Regent’s Regulation (Perbup) are also not functioning effectively. Keywords: Terminal Management, Terminal Facilities, Sekapur Sirih Terminal, Transportation Agency